Understanding In Vitro Embryo Development through Classical Germination Measurements: A Case Study of Dragon’s Blood (Croton lechleri Müll Arg.) - de Albuquerque, Janai Pereira; Ribeiro-Oliveira, João Paulo; de Oliveira-Júnior, João Bosco; da Silva Costa, Frederico Henrique; Amaral da Silva, Edvaldo Aparecido [UNESP] (MDPI, 2023)
Sample size fluctuation and the restriction of measurements that demonstrate kinetics (typical of physiological processes) are two of the largest inferential constraints in studies on embryonic development in vitro. Thus, we hypothesize that a practical and robust way of aggregating knowledge on aspects of embryonic development in vitro is to use measurements based on the binary counting component. These are typically used to measure the germination process (intraeminal embryonal development). Our biological model was Dragon’s blood (Croton lechleri Müll Arg.), a species native to the Amazon with great socioeconomic impact. Matrices originating from two populations (one native and another cultivated) were the source of biological material. From this material, we studied five sampling densities (5, 25, 50, and 100 embryos), forming a 2 × 4 factorial ANOVA. Among the measurements studied, the coefficient of variation of time, uncertainty, and the synchronization index were the most sensitive to sample-size fluctuation. The synchronization index, however, also proved to be an interesting measurement to detect the parental effect related to the place of occurrence of the matrices. The embryonic development ability, mean development time, and mean development rate were not affected by fluctuations in the sample size or the origin of the material, demonstrating highly conserved traits of the species. Finally, in general, the measurements based on binary counting demonstrated robustness for modeling embryonic growth.
Keywords: embryo development; functional traits; growth and development; modeling and measurements; sample size